Shalom Montreal: Stories and Contributions of the Jewish Community, McCord Museum - Nantel, Sarah (Archivaria, 2018)
Shalom Montreal: Stories and Contributions of the Jewish Community. McCord Museum, Montreal, Quebec. 3 May – 11 November 2018. Curated by Guislaine Lemay.